Effects of dietary Vachelia karroo leaf meal inclusion on meat quality and histological parameters in pedi bucks fed a Setaria verticillata hay-based diet - Brown, D.; Ng'ambi, J. W. (Applied ecology and environmental research, 2019)
The objective of this study was to investigate the effect of dietary Vachellia karroo leaf meal inclusion on growth performance, meat quality and histological parameters in bucks. A total of thirty yearling Pedi bucks with a mean initial body weight of 16.7 ± 3.3 kg were randomly assigned to five treatments in a completely randomized design. Vachellia karroo leaf meal inclusion levels of 20, 25, 30, 40 and 50% were fed to the animals for 60 days. The results showed that dietary treatments had no effect on the final live weights and average daily gains of bucks. Similarly, yields of different carcass components and meat sensory attributes were not affected by the V. karroo. Bucks fed 25% V. karroo leaf meal had higher meat L* values than those on diets 30 or 40% inclusion levels. The livers of bucks fed 20, 25 or 30% V. karroo leaf meal were not adversely affected. However, severe hepatocyte degeneration was noticed in the liver tissues of bucks fed 40 or 50% leaf meal. Dietary V. karroo did not cause any serious damage to the kidneys of the bucks. Thus, V. karroo leaf meal inclusion levels of 20 to 30% are recommended.
Article published in the Applied Ecology and Environmental Research. vol 17 (2)
Keywords: Goats; Tannin; Carcass characteristics; Sensory evaluation; Acacia; Animal feeding; Goat meat-Quality; Animal production